TINJAUAN TERHADAP PENJUALAN MASKER BEKAS DITINJAU DARI UNDANG-UNDANG PERLINDUNGAN KONSUMEN (STUDI KASUS: PUTUSAN NOMOR 444/PID.SUS/PN.BDG) - Putribani Anak Haki; Mariske Myeke Tampi (Jurnal Hukum Adigama, 2021)
Consumer protection having tremendous scope for consumer protection indeed guarantees the rights of the community as a consumer of both goods and services. One form of consumer protection is the consumer protection of medical masks. Nowadays, medical masks are recognised as a need in the middle of Covid-19 pandemic which was formally laid down by the government through the Presidential Decree number 11 year 2020. Nevertheless, there are still business doers that obtain a personal gain by an unkind manner amid this condition, such as the sale of recycled medical masks which were never meant to be used more than once. This study will use the court ruling number 444 / pid.sus / 2020 / pn.bdg which would be studied based on Indonesian consumer protection law. This study used a normative juridical method with the Indonesian consumer protection approach and court ruling approach.